Multiculturalism and social assistance - GAVRILĂ-ARDELEAN, Mihaela (2023)
The scientific approach started from the need to include in a university collection theoretical and practical aspects in the field of social work. Titled Multiculturalism and Social Assistance, this first volume is published in English so that international specialists can find a common language in social work.The volume brings together under the term “multiculturalism” specialists in the social work area, from practitioners to university professors who come from different countries and cultures, into a unitary whole of the common culture of social assistance, which deserves international recognition.